Study of the parameters atmospheric boundary layer in the development of cloud convection - Nina Evgenievna Danilova; Lyudmila Mikhailovna Kulygina; Yuliya Aleksandrovna Semenova; Robert Gurgenovich Zakinyan (Наука. Инновации. Технологии)
One of the types of vertical movements in the atmosphere is convection. Convective motions arise in an unstable stratified atmosphere under the influence of atmospheric fronts or orographic features of the region. Free convection is the root cause of almost all movements in the atmosphere. Orographic features affect the development of convection in two ways: indirectly by deformation of the frontal zones with the subsequent development of baric formations or directly during the flow of airflow through mountain obstacles. A very important role in the development of cloud convection is played by the parameters of the surface layer, such as: the dynamic factor due to orography; Thermal factor due to initial overheating. In this paper, cloud convection is not a perturbed state with respect to rest, but is represented by an average motion caused only by a fluctuation in air density, which depends on the temperature and the mass fraction of water vapor. This consideration is more consistent. The presented calculations show that the module of the total air velocity for thermal convection of dry air and the size of the convective cell depend signiicantly on the velocity of the ascending streams at the ground, caused by the relief of the terrain, and also the surface parameters.